1995
DOI: 10.1074/jbc.270.41.23906
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid X Receptor Acts as a Hormone Receptor in Vivo to Induce a Key Metabolic Enzyme for 1,25-Dihydroxyvitamin D3

Abstract: We demonstrate here that RNA levels of 25-hydroxyvitamin D 3 -24-hydroxylase (24-(OH)ase), a key catabolic enzyme for 1,25-dihydroxyvitamin D 3 , are increased by a highly selective retinoid X receptor (RXR) ligand, LG100268, in mice within hours. Correspondingly, upon LG100268 treatment, kidney 24-(OH)ase enzymatic activity increases 5-10-fold. The endogenous retinoid hormones, all-trans-retinoic acid and 9-cis-retinoic acid, and the synthetic retinoic acid receptor-selective compound, TTNPB, also stimulate 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 27 publications
(26 reference statements)
3
26
1
Order By: Relevance
“…Allegretto et al were able to show that a synthetic rexinoid (RXR-selective agonist) could stimulate transcription from CYP24 promoter sequences in vitro when cotransfected with RXRg or RARg. 54 While interestingly, this does not adequately explain the retinoid antagonism of vitamin D effects observed in this study or in the recent work by Rohde and DeLuca. 49 Further research needs to be done to confirm results and hypotheses generated from in vitro work with retinoids and vitamin D, and to test their validity in complex living systems.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Allegretto et al were able to show that a synthetic rexinoid (RXR-selective agonist) could stimulate transcription from CYP24 promoter sequences in vitro when cotransfected with RXRg or RARg. 54 While interestingly, this does not adequately explain the retinoid antagonism of vitamin D effects observed in this study or in the recent work by Rohde and DeLuca. 49 Further research needs to be done to confirm results and hypotheses generated from in vitro work with retinoids and vitamin D, and to test their validity in complex living systems.…”
Section: Discussioncontrasting
confidence: 80%
“…The retinoid modulation of vitamin D metabolism observed by Trechsel and Fleisch was in a kidney cell culture model 53 and, to our knowledge, has not been confirmed in vivo. The subtle changes in CYP24 expression (3.1-fold induction with 10 mg/kg 9cRA and 2.1-fold induction with 1 mg/ kg 9cRA) reported by Allegretto et al were measured using Northern blotting analysis in the kidneys of BALB/c strain mice, 54 while our study utilizes the more sensitive tool of real-time PCR analysis of mRNA expression in A/J mice. Allegretto et al were able to show that a synthetic rexinoid (RXR-selective agonist) could stimulate transcription from CYP24 promoter sequences in vitro when cotransfected with RXRg or RARg.…”
Section: Discussionmentioning
confidence: 91%
“…In our study, a persistently elevated plasma RA level in Atlantic salmon decreased plasma CTR levels by at least 80%. All-trans RA and 9-cis RA are potent stimulators of Cyp24 expression in vivo in mice (Allegretto et al 1995). A similar mechanism in salmon could explain the decrease in plasma CTR levels at day 5 and 7 in RA-treated fish.…”
Section: Discussionmentioning
confidence: 87%
“…RA was found to stimulate Vdr expression in both tumour and non-tumour bone cells of rats (Petkovich et al 1986) and mouse (Suzuki et al 1993). RA also increases the expression of the VD catabolising enzyme 25(OH)D 3 -24-hydroxylase (Cyp24a1; Allegretto et al 1995), and synergistic effects were shown between RA and CTR in their effect on rat renal CYP24A1 activity (Reinhardt et al 1999). Frankel et al (1986) found that chronically VA-overdosed rats had increased osteoclast activity, reduced osteoid formation and reduced circulating levels of 25(OH)D 3 , and that VD-overdosed animals lowered their serum Ca and serum 25(OH)D 3 after a moderate dose of VA.…”
Section: Introductionmentioning
confidence: 99%
“…In some experiments transfected yeast (Saccharomyces cerevisiae) extract enriched in human VDR (28) and human RXR (29) were added to the reaction mixture, either in the presence or absence of primate cell nuclear extract. The double-strand oligonucleotides used as specific competitors in EMSAs were prepared by annealing complementary sequence.…”
Section: Methodsmentioning
confidence: 99%